Clinico-demographic Profile of Coronavirus Infection among Bangladeshi Children: A Tertiary Care Hospital Study - Ghosh, Uzzal Kumar; Sultana, Azmeri; Ghosh, Nobo Krishna; Akram, Arifa; Ahmed, Erfan; Rana, Imam Haidar; Choudhury, Ahmed Murtaza (Bangladesh Journal of Infectious Diseases, 2020)
Background: Variation and atypical presentation of COVID-19 in Bangladeshi children has been noticed. Objective: The purpose of the present study was to see the clinical and demographic features for easy and early identification of coronavirus infection. Methodology: This descriptive cross-sectional study was done at Dr. MR Khan Shishu Hospital & ICH, Dhaka, Bangladesh from April 2020 to August 2020. The suspected case of coronavirus infection was advised RT-PCR and symptomatic home treatment was given. Hospitalization was done in severe cases. Then diagnosis was made by clinical symptoms plus investigations and appropriate treatment was given. Then RT-PCR was done among them in suspected cases. Other investigations were done accordingly. Results: Among the 236 cases RT-PCR positive was found 71(30.08%) cases. The male-female ratio was 1.7:1. Mostly was 1 year to 2 years (21.13%) and 5 years to 10 years (21.13%). About twenty percent was asymptomatic, 80.28% was symptomatic, co-infections was 29.58%, and co-morbidities was 8.45%. The duration of RT-PCR was positive up to two, four, six, and more than six weeks 49.30%, 30.99%, 16.90%, and 2.82% respectively. Fever (80.28%), cough (45.07%), sore throat (33.80%), runny nose (29.58%), anorexia (28.17%), convulsion (25.35%), respiratory distress & acute diarrhea (15.50%), weakness (14.08%), paralytic ileus, rash and acute abdomen (4.23%). Conclusion: COVID-19 in Bangladeshi children are found with a variety of clinical presentations; unlike that of the adult. Bangladesh Journal of Infectious Diseases, October 2020;7(suppl_2):S16-S21